ANALYSIS OF FACTORS AFFECTING WORK READINESS BASED ON STUDENT PERCEPTION USING PARETO ANALYSIS - Hermas Gunawan; Wiyogo (Jurusan Pendidikan Teknologi Dan Kejuruan, 2023)
The analysis of students' perceptions of job readiness was conducted using the Pareto analysis method. The results showed that interpersonal skills were the main factor that most influenced students' perceptions of job readiness, with a frequency of 40%. Hard skills had a frequency of 37%, while soft skills had a frequency of 23%. Interpersonal skills are necessary for building good relationships between employees and superiors, colleagues, and customers. Hard skills determine whether employees have the technical skills required in their field of work, while soft skills are essential in problem-solving and making the right decisions in the workplace. Therefore, students need to improve their interpersonal skills by training skills such as communication, leadership, collaboration, and empathy. Hard skills can be improved by increasing technical knowledge and direct practice in the desired field of work. Soft skills can be honed through exercises in creativity, innovation, data analysis, and conflict resolution. Students also need to understand the importance of having a balanced set of interpersonal, hard, and soft skills to prepare themselves well for the job market. They should take advantage of opportunities to participate in extracurricular activities, internships, or relevant training and certification courses. By improving their interpersonal, hard, and soft skills, students will be able to strengthen their perception of job readiness and increase their chances of getting good jobs and succeeding in the future. Furthermore, companies can obtain more qualified and productive employees, helping them to achieve their business goals more effectively.Keywords: Student Perceptions, Job Readiness, Interpersonal Skills, Hard Skills, Soft Skills, Pareto, Gaps